Compliance with Guidelines Recommending the Use of Simulation for Neonatal and Infant Resuscitation Training in Austria - Mileder, L. P.; Urlesberger, B.; Schwindt, J.; Simma, B.; Schmölzer, G. M. (Klinische Pädiatrie, 2014)
Current international resuscitation guidelines recommend simulation for the training of neonatal and infant resuscitation. We aimed at assessing compliance rates with these recommendations in Austria.We performed a national questionnaire survey among 31 neonatal institutions in Austria.25 questionnaires (80.6%) were analyzed. 22/25 institutions (88%) used simulation as an instructional modality. 8 institutions (32%) had access to medical simulation centers, with 6/8 being used for neonatal and infant resuscitation training. Simulation equipment was available at 17/25 institutions (68%), with a median of 1 part-task trainer (0–2), 2 low-fidelity resuscitation mannequins (0–10), and 0 high-fidelity patient simulators (0–7). Resuscitation training frequency varied widely, ranging from one training per month to one training per year. 5 simulation centers utilized interdisciplinary resuscitation training with other medical specialties and team training including physicians and nursing staff. Of the 17 institutions with simulation equipment at their disposal, 8 (47.1%) carried out interdisciplinary training and 13 (76.5%) performed team-oriented training sessions.The majority of surveyed institutions adopted simulation for neonatal and infant resuscitation training according to current guidelines and had simulation equipment at their disposal. However, educational practice varied widely, especially in regard to training frequency. Therefore, we suggest a national consensus agreement on best practices in simulation-based neonatal and infant resuscitation training.
Keywords: newborn; infant; resuscitation; education; simulation